Docosahexaenoic acid,22:6n-3: Its roles in the structure and function of the brain - Mallick, Rahul; Basak, Sanjay; Duttaroy, Asim K. (International journal of developmental neuroscience, 2019)
•Docosahexaenoic acid,22:6n-3 (DHA) is important for brain growth and development.•Dietary intake of DHA is recommended throughout the life cycle.•DHA and its metabolites are involved in the brain structure and function.•DHA deficiency is observed in brain disorders.•Clinical trials of DHA supplementation improve brain function. Docosahexaenoic acid,22:6n-3 (DHA) and its metabolites are vital for the structure and functional brain development of the fetus and infants, and also for maintenance of healthy brain function of adults. DHA is thought to be an essential nutrient required throughout the life cycle for the maintenance of overall brain health. The mode of actions of DHA and its derivatives at both cellular and molecular levels in the brain are emerging. DHA is the major prevalent fatty acid in the brain membrane. The brain maintains its fatty acid levels mainly via the uptake of plasma free fatty acids. Therefore, circulating plasma DHA is significantly related to cognitive abilities during ageing and is inversely associated with cognitive decline. The signaling pathways of DHA and its metabolites are involved in neurogenesis, antinociceptive effects, anti‐apoptotic effect, synaptic plasticity, Ca2+ homeostasis in brain diseases, and the functioning of nigrostriatal activities. Mechanisms of action of DHA metabolites on various processes in the brain are not yet well known. Epidemiological studies support a link between low habitual intake of DHA and a higher risk of brain disorders. A diet characterized by higher intakes of foods containing high in n‐3 fatty acids, and/or lower intake of n‐6 fatty acids was strongly associated with a lower Alzheimer's Disease and other brain disorders. Supplementation of DHA improves some behaviors associated with attention deficit hyperactivity disorder, bipolar disorder, schizophrenia, and impulsive behavior, as well as cognition. Nevertheless, the outcomes of trials with DHA supplementation have been controversial. Many intervention studies with DHA have shown an apparent benefit in brain function. However, clinical trials are needed for definitive conclusions. Dietary deficiency of n‐3 fatty acids during fetal development in utero and the postnatal state has detrimental effects on cognitive abilities. Further research in humans is required to assess a variety of clinical outcomes, including quality of life and mental status, by supplementation of DHA.